If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 + 8 = x + 5 Reorder the terms: -2 + 8 + 6x = x + 5 Combine like terms: -2 + 8 = 6 6 + 6x = x + 5 Reorder the terms: 6 + 6x = 5 + x Solving 6 + 6x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 6x + -1x = 5 + x + -1x Combine like terms: 6x + -1x = 5x 6 + 5x = 5 + x + -1x Combine like terms: x + -1x = 0 6 + 5x = 5 + 0 6 + 5x = 5 Add '-6' to each side of the equation. 6 + -6 + 5x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 5 + -6 5x = 5 + -6 Combine like terms: 5 + -6 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| s^3+4*s^2+10*s+40=0 | | 4sin(3x)=2 | | X-4=-3.4 | | v/5=85 | | 1234321n^67= | | 9.5w=-104.5 | | 4p^2+5p-q=0 | | 15x-5+3= | | 7m-20=22 | | -2x+5x-9=3(t-4)-5 | | 48+10y-3y^2=0 | | 29+4.50x=42.50 | | 2(3x-1)+6x=37-x | | 2x=(x^2-35) | | 5z+5+z=-7 | | -5(-1+2x)=-45 | | x/y=8/14 | | 1+2y= | | 2x^4-x^3-18x^2+9x=0 | | 5x=-3(-4x+2) | | 5x+8(85-4x)=115 | | (5x-25)e^(x/5) | | 3-6(x+3)=33 | | -3(-5x+3)=96 | | 29+4.50=42.50 | | x^2+10x+40=5 | | 2.5p=6.25 | | 29x+4.50=42.50 | | 7(-7x+2)=-329 | | 5/2=x-5/4 | | 6x^4-5x^3-12x^2+5x+6=0 | | 48=s |